EFEKTIVITAS MUSYAWARAH GURU MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKANKOMPETENSI PEDAGOGIK GURU TINGKAT SEKOLAH MENENGAH ATAS - Sera Yuliantini; Yuni Yuni (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2023)
The aims of this research are: 1). Describe the material for teacher deliberations for Islamic religious education subjects in improving the pedagogic competence of Islamic religious education teachers at the senior high school level in Sambas District 2). Describe the role of Islamic religious education teacher deliberations in improving the pedagogic competence of Islamic religious education teachers at the senior high school level in Sambas District 3). Describe the inhibiting factors of Islamic religious education teacher deliberations in improving the pedagogical competence of high school level teachers in Sambas District. This study uses a qualitative approach and a type of phenomenological research. Data collection techniques are 1). Observation techniques, 2). Interview techniques and 3). Documentation technique. Data analysis techniques are 1). Data reduction, 2). Display data, 3). Data verification and drawing conclusions. Data validity techniques are source triangulation and member checks. The results of the study are: 1) The material in Islamic religious education subject teacher deliberations in improving the pedagogic competence of Islamic religious education teachers at the senior high school level in Sambas Regency is planning, processes and learning equipment such as making learning programs, using media and methods and learning evaluation, 2) The role of Islamic religious education teacher deliberations in improving the pedagogical competence of high school Islamic religious education teachers in Sambas Regency as reformers, mediators, collaborators, clinical and academic supervisors, evaluators and school developers, along with supporting agencies. 3) The inhibiting factors for teacher deliberations for Islamic religious education subjects in improving the pedagogical competence of high school level teachers in Sambas Regency were the lack of enthusiasm of members in participating in activities due to busyness of teachers, limited sources of funds and the problem of being too far away.